EXTH-53. A BRAIN-PENETRANT MICROTUBULE-TARGETING AGENT THAT DISRUPTS HALLMARKS OF GLIOMA TUMORIGENESIS. (9th November 2020) - Horne, Eric; Vicente Ruiz, Juan J; Cimino, Patrick; Jung, Erik; Xu, Cong; Diaz, Philippe; Hamel, Ernest; Kumasaka, Debra K; Wagenbach, Michael J; Winkler, Frank; Wordeman, Linda G; Holland, Eric; et al.
Abstract: Most cancer therapeutics developed to date are excluded from the brain and are therefore ineffective in treating glioma, the most devastating type of brain cancer in adults. Microtubule targeting agents (MTAs) are indispensable medicines to treat a wide range of solid and hematopoietic tumors, and evidence suggests that glioma is sensitive to MTAs; but most MTAs do not cross the blood-brain-barrier. To address this limitation, we developed a brain-penetrant MTA, ST-401, that inhibited the growth of human glioma in culture at nanomolar concentrations. ST-401 bound to the colchicine site, inhibited tubulin assembly and reversibly reduced microtubule (MT) dynamics. Testing of ST-401 on the NCI 60 cancer cell panel indicated that its anti-tumor activity does not correlate with any of the compounds tested thus far through this platform but showed weak correlations for two MTA that work through distinct mechanisms: taxol (p=0.46) and vinblastine (p=0.34). Thus, ST-401 may kill cancer cells through a novel mechanism related to disruption of MT function. We discovered that ST-401 killed patient-derived (PD) glioma isolates in both mitosis and interphase, and inhibited the formation of tumor microtubes, MT-rich structures that connects glioma cells to a network that is resistant to standard therapies. Pharmacokinetic analysis of ST-401 in mice shows brain penetration reaching antitumor concentrations, and in vivo testing of ST-401 in a xenograft model demonstrated significant antitumor activity. In an immunocompetent mouse model of platelet-derived growth factor B-driven glioma, ST-401 significantly enhanced the therapeutic efficacies of standard care therapies temozolomide and radiation therapy. Our study identified novel aspects of glioma tumorigenesis that exhibit enhanced sensitivity to MTAs and shows that the brain-penetrant MTA, ST-401, represents a promising chemical scaffold to develop therapeutics for the treatment of patients diagnosed with glioma.